Thin-film transistors with active layers of zinc oxide (ZnO) fabricated by low-temperature chemical bath method - Cheng, HC; Chen, CF; Lee, CC (My University, 2006)
Thin-film transistors (TFTs) with active channel layers of zinc oxide (ZnO) using a low-temperature chemical bath deposition have been studied. The ZnO films were fabricated on the defined-areas of bottom-gate type TFTs plate by immersing in a chemical bath containing zinc nitrate (Zn(NO3)(2).6H(2)O) and dimethylarnmeborane (DMAB) aqueous solution at 60 degrees C. Silicon oxide (SiO2) was used as the gate insulator. Produced TFTs plate was dried in the air at 100 degrees C, specially, without any further annealing. Current-voltage (I-V) properties measured through the gate infer that the ZnO channel is n-type. Devices were achieved that I-on/I-off ratio was more than 10(5), for which the channel mobility on the order of 0.248 cm(2) V-1 s(-1) has been determined. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chemical bath method; zinc oxide; thin-film transistors; active channel layers